Space shuttle stories : firsthand astronaut accounts from all 135 missions - Jones, Tom, 1955 January 22- (Smithsonian Books, 2023)
"Experience all 135 NASA space shuttle missions ever flown through the words of the astronauts themselves in this spectacularly illustrated volume with more than 600 photos from the NASA archives"--